2013
DOI: 10.1016/j.biopsych.2012.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Effects of Voluntary Exercise on Memory and the Older Brain

Abstract: Background Physical exercise in early adulthood and mid-life improves cognitive function and enhances brain plasticity, but the effects of commencing exercise in late adulthood are not well-understood. Method We investigated the effects of voluntary exercise in the restoration of place recognition memory in aged rats and examined hippocampal changes of synaptic density and neurogenesis. Results We found a highly selective age-related deficit in place recognition memory that is stable across retest sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 52 publications
6
49
1
3
Order By: Relevance
“…Consistent with the findings of Redila and Christie [75], who found that in rats, running is not correlated with granule cell dendritic complexity, others found that exercise restores the loss of intra-hippocampal connectivity [114,115], neurogenesis [105,112,114,116] and BDNF and TrkB levels [114] that accompanies sedentary aging [67]. Temporally, aging suppresses in vitro neural stem cell proliferation in mice beginning at six months of age [117].…”
Section: Physical Activity Partially Reverses the Age-related Declsupporting
confidence: 81%
“…Consistent with the findings of Redila and Christie [75], who found that in rats, running is not correlated with granule cell dendritic complexity, others found that exercise restores the loss of intra-hippocampal connectivity [114,115], neurogenesis [105,112,114,116] and BDNF and TrkB levels [114] that accompanies sedentary aging [67]. Temporally, aging suppresses in vitro neural stem cell proliferation in mice beginning at six months of age [117].…”
Section: Physical Activity Partially Reverses the Age-related Declsupporting
confidence: 81%
“…The precise mechanism of this readiness is made challenging by the host of pre-synaptic enhancement of neurotransmitter release and post-synaptic N-methyl-D-aspartate receptor (NMDA) and α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor changes as well as important downstream activity (e.g., cAMP response element-binding protein; CREB) associated with exercise-induced BDNF activity (Christie et al, 2008; Vaynman et al, 2004), all of which could play a role in long-term potentiation effects. In addition, in terms of longer-term structural changes, exercise appeared to reverse hippocampal degeneration and declining hippocampal network efficiency in aged animals, with enhancement of presynaptic densities and greater connectivity (Siette et al, 2013). These changes appear to explain the observed improvements in recognition memory associated with exercise in animals (Cotman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise has been reported to contribute to further beneficial effects on the memory domain 32,36,48. The results of an animal study investigating the effects of 12 weeks of voluntary running on the restoration of place recognition memory in 20-month-old rats emphasized the unique synaptic effects of exercise on the aged brain and their specific relevance to the hippocampal-based system for place recognition memory 63. Dancing involves paying attention to music and signals while envisaging the next movement, and these feature may help patients to perform better in the verbal fluency category 50.…”
Section: Discussionmentioning
confidence: 99%